The effect of nanosized carbon black on the morphology and sc-CO2 foaming behavior of LLDPE/PS blends at semi-solid state. (March 2018) - Zhang, Shaofeng; Zhang, Guangchun; Qiu, Jian; Jiang, Zhiwei; Xing, Haiping; Li, Minggang; Tang, Tao
Abstract: The influences of nanosized carbon black (CB) on the morphology of immiscible cocontinuous LLDPE/PS blends and their foaming behavior under the sc-CO2 batch foaming was studied. The morphologies and cellular structures of LLDPE/PS blends and LLDPE/PS/CB nanocomposites were characterized by scanning electron microscope (SEM). The results indicated that the introduction of CB nanoparticles could effectively improve foaming ability of LLDPE/PS=50/50 blends, when enough amount of CB nanofillers was added. This was ascribed to the morphology transformation from cocontinuous structure to sea-island structure due to the presence of CB nanofillers. Furthermore the critical amount of CB for dramatically improving the foaming capacity depended on the foaming temperature. In contrast, the addition of CB in the LLDPE/PS blends with spherical dispersed phase (such as 80/20 or 20/80, by weight) did not dramatically change the foaming behavior of the blends. Graphical abstract: Highlights: The addition of carbon black nanoparticles changed the morphology of LLDPE/PS blends. The phase structure of LLDPE/PS blend affected the foaming behavior of the blends. The presence of enough amount of CB enhanced CO2 batch-foaming capacity of the blends at semi-solid state.